The efficacy of clobetasol propionate with varying dilutions of emollient determined by histamine wheal suppression test - M Barathi; Reena Rai; C R Srinivas (Wolters Kluwer Medknow Publications, 2011)
Background: The ability of steroids to reduce the histamine wheal was used to assess the efficacy of topical clobetasol propionate with varying dilutions of emollients. Aim: To determine the wheal-suppressing ability of topical clobetasol with varying dilutions of emollient. Materials and Methods: It was a double-blinded randomized study. Twenty-five volunteers were included in the study. Five syringes of 5 ml were taken and the syringes were loaded with either clobetasol propionate 0.05%, emollient, or clobetasol propionate with emollient in dilutions of 1:1, 1:2, and 1:3. The syringes were coded 1 to 5. Five squares of 3 × 3 cm were marked on the flexor aspect of the forearm of the volunteers. After randomization, half fingertip unit of the cream was applied within each square uniformly. Three hours later histamine prick test was performed by the standard method. The wheal was measured after 15 min and the results were recorded. After decoding, results were statistically analyzed by analysis of variance. Result: The decrease in wheal suppression of steroid with emollient (1:1) was same as topical steroid and the wheal suppression decreased with increasing dilutions of steroid. Conclusion: We conclude that steroids and emollients can be mixed in equal proportion (1:1) and the effect is same as steroid alone and increasing dilution of steroids with emollients was not effective in suppressing the wheal.